Blow-up of solutions to a nonlinear nonlocal reaction-diffusion system with time-dependent coefficients and inner absorption terms - Ouyang, Baiping (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
Global existence and blow-up of solutions to a nonlinear nonlocal reaction-diffusion system with time-dependent coefficients and inner absorption terms under nonlinear boundary conditions are studied.Energy expressions are formulated.By using the technique of Sobolev inequalities and other differential ones,the energy satisfying a differential inequality under certain conditions is deduced.Finally,the global existence and lower bound estimates of blow up time are obtained respectively.